The Relationship between Dietary Patterns, Protein Adequacy Levels, Energy Adequacy Levels and Stress Levels with the Nutritional Status of Female Students at Bangun Cipta Vocational School, Rumbia, Central Lampung, 2024 - Wati, Indah Rahma; Kustiani, AI; Hervidea, Radella (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
Adolescence involves rapid growth, increasing protein and energy needs. A survey on April 14, 2024, at Bangun Cipta Rumbia Vocational School in Central Lampung assessed 10 female adolescents' nutritional status using BMI/U. Results showed 2 had poor nutritional status, and 7 had normal status, though their diet did not fully meet balanced nutrition guidelines. This study examined the relationships between diet, protein adequacy, energy adequacy, stress levels, and nutritional status. A descriptive cross-sectional design surveyed 78 out of 97 females aged 16-19 years from classes X and XI. Data collected through FFQ, Food Recall, Depression Anxiety Stress Scale, Microtoise were analyzed using Pearson and Spearman tests. Findings indicated significant relationships between diet, protein, energy adequacy with nutritional status (p-value 0.05), no significant link between stress levels and nutritional status. It is recommended that schools educate students on healthy eating and portion sizes.